Ectopic calcification and formation of mineralo-organic particles in arteries of diabetic subjects - Wu, Cheng-Yeu; Martel, Jan; Young, John D. (Scientific reports, 2020)
Vascular calcification occurs in various diseases including atherosclerosis, chronic kidney disease and type 2 diabetes but the mechanism underlying mineral deposition remains incompletely understood. Here we examined lower limb arteries of type 2 diabetes subjects for the presence of ectopic calcification and mineral particles using histology, electron microscopy and spectroscopy analyses. While arteries of healthy controls showed no calcification following von Kossa staining, arteries from 83% of diabetic individuals examined (19/23) revealed microscopic mineral deposits, mainly within the tunica media. Mineralo-organic particles containing calcium phosphate and proteins such as albumin, fetuin-A and apolipoprotein-A1 were detected in calcified arteries. Ectopic calcification and mineralo-organic particles were observed in a majority of diabetic patients and predominantly in arteries showing hyperplasia. While a low number of subjects was examined and information about disease severity and patient characteristics is lacking, these calcifications and mineralo-organic particles may represent signs of tissue dysfunction.